Separation of catechin epimers by complexation using ion mobility mass spectrometry. (20th February 2015) - Troć, Anna; Zimnicka, Magdalena; Danikiewicz, Witold
Abstract : Ion mobility coupled with mass spectrometry provides a fast and repeatable method to separate catechin epimers by previous complexation with selected chiral modifiers and transition metals. Several combinations with chiral ligands such as D‐ and L‐amino acids and/or additional metal cations, chiral crown ethers, tartaric acid and heptakis(2, 6‐di‐O‐methyl)‐ β ‐cyclodextrin were screened for their ability to affect the separation efficiency. The clusters having the form of [2M + D‐amino acid + Cu 2+  − 3H] − (M stands for (−)‐epicatechin or (+)‐catechin) showed improvement in stereodifferentiation between two epimeric catechins in comparison to the analysis of pure epimers, where no separation was observed or the separation was hampered by the formation of mixed dimer complexes. Among various examined D‐amino acids only those possessing hydrophobic side chains induced the improvement of separation efficiency. The best peak‐to‐peak resolution (Rp–p ) was determined to be 0.71 for [2M + D‐Leucine + Cu 2+  − 3H] − clusters. Copyright © 2015 John Wiley & Sons, Ltd.